Delivery of Antigen to CD8+ Dendritic Cells by Fusing Antigen With Formyl Peptide Receptor-Like 1 Inhibitor Protein Induces Antitumor Immunity - Chiang, Chen-Yi; Wu, Chiao-Chieh; Chen, Yi-Jyun; Liu, Shih-Jen; Leng, Chih-Hsiang; Chen, Hsin-Wei (Frontiers in Immunology, 2019)
A major challenge for vaccine development is targeting antigens to dendritic cells (DCs) in vivo, enabling cross-presentation, and inducing the memory responses. Fcγ receptors (FcγRs) are expressed on many cell types including DCs. Therefore, targeting of antigen to DCs via FcγRs is an attractive strategy for vaccine development. This study employ formyl peptide receptor-like 1 inhibitory protein (FLIPr), an FcγR binding protein secreted by Staphylococcus aureus, to deliver antigen to DCs. Our results show that FLIPr is a competent vehicle in delivering antigen to CD8+ DCs for induction of potent immunities without extra adjuvant formulation. Fusion antigen with FLIPr enables effective antigen presentation on both MHC class II and class I to induce memory T cell responses. Altogether, using FLIPr as an antigen delivery vector has great potential to apply antigens for cancer immunotherapy as well as other infectious disease vaccines.